The Application of a Microcontroller based Electrofusion Welding Machine - Gencer, Cetin; Gurkan, Serkan (Wydawnictwo Sigma-N O T Sp Z O O, 2011)
The application of a microcontroller based electrofusion welding machine has been carried out in this paper. The purpose of this paper is to check the voltage rate which the welding element needs, in a required interval. In order to make safer and better quality welding, features such as bar code reading, welding process parameters memory, the measurement of ambient temperature and internal device temperature. True RMS measurement and real time clock have been added to the system. Electrofusion welding machine, which has been designed after various tests, is thought to be cheaper than the ones on the market, to have high output voltage stability and to operate efficiently in welding electrofusion fittings.
Zastosowanie mikrokontrolera do sterowania elektrodyfuzyjn? maszyn? spawalnicz?
Keywords: Electrofusion welding; Polyethylene; Microcontroller; True RMS